Understanding Schadenfreude in Politics: The Role of Big Five Personalities and Empathy - Ibnu Asqori Pohan; Lusy Asa Akhrani; Ika Herani; Rana Agnaza; Ryan Ady Marsa Baruna (Eduvest - Journal of Universal Studies, 2024)
The euphoria of the Indonesian election has been replaced by an escalation of the conflict that is increasingly evident in society. The community seems to be looking for gaps in political figures and making jokes, both opponents and friends, even parties who are not part of the horizontal political conflict vortex. There is a phenomenon in a society where political events are used as material for good jokes and come from mistakes, politicians' mistakes become laughing stock, even being distributed as material for jokes together. The crisis of empathy is thought to make this phenomenon appear in society, but personality can also encourage the emergence of this behavior. This study aims to determine the role of empathy and personality in this case the big five personalities of voters against schadenfreude in election voters. Empathy is measured by the Interpersonal Reactivity Index scale, schadenfreude is measured by Schadenfreude, while the Big Five Inventory (BFI) scale is used to measure personality. 330 respondents were obtained in this study. This study uses a simple regression analysis and stepwise regression. The results of this study indicate that there is no role of empathy for schadenfreude in voters. Big Five Personality Traits have a stimulating role and a partial role towards schadenfreude, namely agreeableness, neuroticism, and openness traits. While the stimulant role between the Big Five Personality Traits on empathy was found in, there is a role partially between the traits agreeableness, neuroticism, conscientiousness, and openness to Schadenfreude to voters.